1995
DOI: 10.1111/j.1365-2958.1995.tb02338.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the lincomycin‐production gene cluster of Streptomyces lincolnensis 78‐11

Abstract: The lincomycin (LM)-production gene cluster of the overproducing strain Streptomyces lincolnensis 78-11 was cloned, analysed by hybridization, as well as by DNA sequencing, and compared with the respective genome segments of other lincomycin producers. The lmb/lmr gene cluster is composed of 27 open reading frames with putative biosynthetic or regulatory functions (lmb genes) and three resistance (lmr) genes, two of which, lmrA and lmrC, flank the cluster. A very similar overall organization of the lmb/lmr clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
158
0
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(163 citation statements)
references
References 61 publications
3
158
0
2
Order By: Relevance
“…It was suggested that LmbU may have a regulatory function, but no experimental evidence is available so far to support this (Peschke et al, 1995).…”
Section: Resistance and Regulatory Genesmentioning
confidence: 99%
“…It was suggested that LmbU may have a regulatory function, but no experimental evidence is available so far to support this (Peschke et al, 1995).…”
Section: Resistance and Regulatory Genesmentioning
confidence: 99%
“…The processing site of the GFOR presecretory protein between amino acid residues 52 and 53 is marked by an arrow. MocA and ORF334, putative rhizopine dehydrogenases of Rhizobium meliloti (24); DDP-DH, phtalic acid dehydrogenase from Pseudomonas putida (45); GalDH, galactose dehydrogenase from Pseudomonas fluorescens (46); StrI, putative protein in streptomycin biosynthesis from Streptomyces griseus (47); BvRed, biliverdin reductase from rat kidney (48); IDH, inositol dehydrogenase from B. subtilis (36); LmbZ, putative gene product of lmbZ of lincomycin biosynthesis from Streptomyces lincolnensis (49).…”
Section: Revised Gfo Sequence and Prediction Of The Secondarymentioning
confidence: 99%
“…1B), sibiromycin, anthramycin, and tomaymycin is L-tyrosine (3,10). The first two steps of this transformation have been biochemically characterized in the lincomycin A biosynthesis (10,25,26). However, the assignment of the subsequent steps remained difficult due to the lack of significant similarity of the ORFs identified with functionally known enzymes.…”
mentioning
confidence: 99%